PHYSICAL EDUCATION TEACHING PRACTICE IN ELEMENTARY SCHOOLS: AN INVESTIGATION IN THE FAR NORTH OF THE COUNTRY (Fiep Bulletin - online, 2012)
The aim of the study was to know the pedagogical practice developped by novice physical education teachers in the teaching system of schools in Boa Vista county – RR, Brazil. Thirty both-sex teachers, with up to two years of experience were interviewed. The data of the interview was analyzed trough the content analysis, in the method of categorization (BARDIN, 2002). According to the results, the teaching plan executed by the teacher is based on the country curriculum, but, in the pedagogical practice, there is a great difficulty in the materialization. Other problems affect this practice, like the participation of teachers of other disciplines in the construction and execution of this plan. It is concluded que changes are needed in the conducts adopted by these social actors, besides a bigger approximation of the teaching institutions with the necessary practice of the beginners, since the aim of the formal teaching is to form the critical autonomous citizen, facing the challenges of living in society.
Keywords: school physical education; pedagogical practice; initial formation of teachers